An organisation development intervention in a previously disadvantaged school in the Eastern Cape - Mitchell, Pauline (Rhodes University, Faculty of Education, Department of Education, 2005)
"We often spend too much time coping with problems along our path that we forget why we are on that path" Peter Senge This study describes and analyses the implementation of Organisation Development (OD) to a previously disadvantaged school. OD is a relatively new method of planned change in South Africa. Unlike more traditional change initiatives, OD promotes collaboration; it tries to involve all members of an organisation in problem solving and decision-making. It is an applied behavioural science discipline dedicated to improving organisations and the people in them. Previously disadvantaged schools in South Africa continue to be disadvantaged. Ten years after the introduction of democracy there have been few changes in some of these schools and some seem to be getting worse. This study was an attempt to introduce a process of planned change to one such school. Since 1994 many changes have been imposed on our schools with new curricula, increased class sizes, changes in systems of assessment and teaching methods and the abolishment of past procedures such as corporal punishment. Teachers have had little say in any of these changes and this has resulted in resistance, resignation, frustration and in many cases a lack of ability to cope. OD was introduced to Acacia High School in the form of a Survey Data Feedback (SDF). An action research process followed and a diagnosis was made followed by action planning and then the execution of a plan. My study follows this process and the implementation of the plan describing its successes. Sadly change was not sustained and I highlight some of the challenges that face the school in order to bring about real long-term improvement in the culture of learning and teaching.
Keywords: Educational change -- South Africa -- Eastern Cape; Education and state -- South Africa -- Eastern Cape; Education -- Social aspects -- South Africa -- Eastern Cape; Education -- South Africa -- Eastern Cape; School improvement programs -- South Africa -- Eastern Cape -- Case studies; Education -- Aims and objectives -- South Africa -- Eastern Cape